THE DOCTRINE OF CONDOLEEZZA RICE AND NEW MIDDLE EAST TODAY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In June 2006, in Tel Aviv, Condoleezza Rice, in the capacity ofSecretary of State, explicitly placed the geopolitical construction of theNew Middle East, or Condoleezza Rice Doctrine, also known as George• Bush Doctrine. Very clearly, the source, interests and objectives of thisconstruction were US state interests in the Middle East region,geopolitically inevitable and naturally extended with the Middle Eastregion. The geopolitical construction, which through "creativedestruction" and “creative chaos" aimed to result in the creation of such aregional geopolitical construction that would be in full accordance withUS state interests and will express, satisfy and materialize them precisely.